Statistical analysis of epidemiologic data - Selvin, S. (New York ; Oxford : Oxford University Press, 2004)
Thoroughly revised throughout, the 3rd edition of this popular text focuses on clear & practical descriptions of statistical methods for the analysis of epidemiologic data.
Previous ed.: 1996.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Epidemiology -- Statistical methods